The Cell Wall Polysaccharides Biosynthesis in Seaweeds: A Molecular Perspective - Shao, Zhanru; Duan, Delin (Frontiers in Plant Science, 2022)
Cell wall polysaccharides (CWPS) of seaweeds play crucial roles in mechanical shear resistance, cell-cell adhesion and the interactions with changeable marine environments. They have diverse applications in food, cosmetics, agriculture, pharmaceuticals and therapeutics. The recent boost of multi-omics sequence analysis has rapidly progressed the mining of presumed genes encoding enzymes involved in CWPS biosynthesis pathways. In this review, we summarize the biosynthetic pathways of alginate, fucoidan, agar, carrageenan and ulvan in seaweeds referred to the literatures on published genomes and biochemical characterization of encoded enzymes. Some transcriptomic data were briefly reported to discuss the correlation between gene expression levels and CWPS contents. Mannuronan C-5 epimerase (MC5E) and carbohydrate sulfotransferase (CST) are crucial enzymes for alginate and sulfated CWPS, respectively. Nonetheless, most CWPS-relevant genes were merely investigated by gene mining and phylogenetic analysis. We offer an integrative view of CWPS biosynthesis from a molecular perspective and discuss about the underlying regulation mechanism. However, a clear understanding of the relationship between chemical structure and bioactivities of CWPS is limited, and reverse genetic manipulation and effective gene editing tools need to be developed in future.